Behaviour of soft Bangkok clay under horizontal loading - Tampubolon, Muslim; Surachat Sambhanpharaksa; Balasubramaniam, A.S.; Ohta, Hideki; Royal Netherland Government (Bangkok : Asian Institute of Technology, 1981)
The influence of stress path, stress system during shearing (testing in compression or extension), stress history and, stress system during consolidation of soft Bangkok clay was studied experimentally under under undrained triaxial extension condition. For this purpose, twenty triaxial extension test which is divided into four series, either isotropic or anisotropic, loading or unloading stress path and having different stress history was carried out. Test results indicated that there is no practical significant difference of the stress-strain and strength behaviour in horizontal loading from loading and unloading stress path. However, the stress-strain and strength behaviour of Bangkok clay was affected by stress history, by testing in compression or extension, as well as the stress system during consolidation.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1981
Keywords: Strains and stresses; Materials -- Dynamic testing; Clay -- Thailand -- Bangkok -- Testing